(untitled) (Coordinates of Public Administration, 2026)
The article provides a comprehensive analysis of the regulatory and organizational mechanism of the activities of military administrations in Ukraine under the legal regime of martial law. The features of the legal status of military administrations as temporary subjects of public power are revealed, the boundaries of their mandate are determined, and the procedural parameters of the exercise of powers are characterized. The legislative principles of the functioning of military administrations are systematized, the practice of the formation and activities of the specified bodies in 2022–2025 is analyzed, and the problematic aspects of the correlation of their competence with the powers of local self-government bodies and local state administrations are outlined. The structural components of the regulatory and organizational mechanism are substantiated, including: legal definition of competence and territorial jurisdiction, procedural registration of administrative decisions, regulation of temporary substitution of self-government powers, coordination with the military command, documentation of administrative acts, and determination of the conditions for termination of activity. The generalization of scientific approaches and the analysis of current legislation allowed us to establish that the legitimacy of the activities of military administrations is ensured through the normative certainty of competence, the time limitation of extraordinary powers, the proportionality of the applied restrictions and the presence of procedural guarantees of accountability. Directions for improving legal regulation are formulated, aimed at the procedural normalization of the transfer and return of powers to territorial communities and preventing the risks of excessive centralization in conditions of prolonged martial law.